Hydrothermal Synthesis and Tunable Multicolor Upconversion Emission of Cubic Phase Y2O3 Nanoparticles - Haibo Wang; Chao Qian; Zhigao Yi; Ling Rao; Hongrong Liu; Songjun Zeng (Advances in Condensed Matter Physics)
Highly crystalline body-centered cubic structure Y2O3 with lanthanide (Ln) codopants (Ln = Yb3+/Er3+ and Yb3+/Ho3+) has been synthesized via a moderate hydrothermal method in combination with a subsequent calcination. The structure and morphology of Y(OH)3 precursors and Y2O3 nanoparticles were characterized by X-ray diffraction and transmission electron microscopy. The results reveal that the Y2O3 nanoparticles possess cubic phase and form the quasispherical structure. The upconversion luminescence properties of Y2O3 nanoparticles doped with different Ln3+ (Yb3+/ Er3+ and Yb3+/ Ho3+) ions were well investigated under the 980 nm excitation. The results show that the Yb3+/Er3+ and Yb3+/Ho3+ codoped Y2O3 nanoparticles exhibit strong red and light yellow upconversion emissions, respectively. It is expected that these Y2O3 nanoparticles with tunable multicolor output and intense red upconversion emission may have potential application in color displays and biolabels.